ANTESEDEN PEMBERDAYAAN KARYAWAN BANK DAN KONSEKUENSINYA TERHADAP KINERJA INDIVIDU - Yuni Siswanti; Anis Siti Hartati (University of Merdeka Malang, 2013)
This study investigated the impact of mediation effect of empowerment to relation among locus of control,organization tenure, education, leadership, and teams strength of team, belief of team, organizational culture,and Leader Member Exchange to employee performance. The Participants were employees (n=134) from someprivate banks in Jogjakarta with purpossive sampling.We used SEM to test hypotheses. Findings showed that:(1) empowerment had direct effect to employee performance (H1) supported), and (2) empowerment becamepartially mediated variable among locus of control, organization tenure, education, leadership, strength ofteam, belief of team, organizational culture, and Leader Member Exchange (LMX) to employee performance(H2) supported. Locus of control, organization tenure, education, leadership, strength of team, belief of team,organizational culture, and Leader Member Exchange had direct effect to employee performance.